Refleksi Putusan Mahkamah Agung Nomor 23 P/HUM/2024: Eskalasi Yudisialisasi Politik dan Politisasi Yudisial dalam Pengujian Norma - Azhumatkhan, syarif Hidayatullah; Tri Firmansyah, Adithya (Academos, 2024)
The lofty goal of realizing an independent judiciary to uphold law and justice is now facing a steep road because in the process, the judiciary is always vis a vis at the crossroads between law and politics. Currently, instead of bringing the issue of interference, the judiciary has become the party that intervenes in the rule-making power, and this has almost reached a culmination point. The latest crucial event is Supreme Court Decision No. 23/P/HUM/2024. The decision changes the meaning of the prerequisite norm of the age limit for Regional Head candidates, which is calculated from the determination of the candidate pair, to be calculated from the inauguration. Starting from the description above, this research aims to explore the meaning of the Supreme Court's activities in the concept of political judicialization and judicial politicization. The research method used is normative (legal) research, with statutory, case, historical, and conceptual approaches. The results of this study are, first, Supreme Court Decision No. 23 P/HUM/2024 shows weaknesses because the arguments given are not sufficient, and the Supreme Court also exceeds its authority by intervening in the legal policy authority of the KPU, this can be interpreted as political judicialization and judicial politicization. Second, the Problems of Supreme Court Decision No. 23 P/HUM/2024 are enough to reflect that there are still legal gaps that must be addressed. So that in the future, in the context of legal reform, it is necessary to integrate one-stop testing of laws and regulations in the Constitutional Court.